People in Personal Learning Networks: Analysing their Characteristics and Identifying Suitable Tools - Rajagopal, Kamakshi; Verjans, Steven; Sloep, Peter B.; Costa, Cristina (Proceedings of the International Conference on Networked Learning, 2012)
In recent years, the concept of a Personal Learning Network (PLN) as a structure to support personal learning has become more and more widespread. A Personal Learning Network refers to the network of people a self-directed learner connects with for the specific purpose of supporting their learning. An effective use of PLNs as learning resources depends on various networking skills of the learners. These skills include content-related skills such as such as being able to engage in conversations and being able to communicate ideas, thoughts and opinions to the listener, but also (ii) skills regarding the process of networking itself to continuously build, maintain and activate PLNs, in particular to be able to identify the experience and expertise of the connections in their PLNs. Relationships for learning in a PLN are often supported through various technical instruments and platforms. Although many technologies are being developed to support learners’ construction and maintenance of their Personal Learning Network, the design is often based on certain assumptions on what learners consider important for their own social learning. However, there has been little investigation on what a learner considers important in a PLN. This article presents the results of a study on the concepts that determine whether a learner considers a contact to be valuable to their learning, the perceived relevance or importance of these concepts to the learner, and the extent to which these concepts are perceived to be supported by current popular networking platforms. The methodology used consists of a two-stage process: a scaffold activity on name generation and abstraction of concepts by participants in a workshop on networking skills, followed by a survey rating the importance of the elicited concepts and their association with 5 chosen PLN-supporting platforms. The conclusions of the study are (i) 18 concepts are generally accepted as driving a learner’s PLN, (ii) that social learning via PLNs still remains very hidden, but reflective activities encourage more control over this type of learning, and (iii) that different social networking platforms fullfil different aspects of the supporting personal learning networks, with the exception of Twitter as a learning platform, that emerges from the study as the most widely applicable tool.